A Novel Role of IL13Rα2 in the Pathogenesis of Proliferative Vitreoretinopathy - Qi, Hui; Dong, Lijun; Fang, Dong; Chen, Lu; Wang, Yun; Fan, Ning; Mao, Xingxing; Wu, Wenyi; Yan, Xiaohe; Zhang, Guoming; Zhang, Shaochong; Lei, Hetian (Frontiers in Medicine, 2022)
Proliferative vitreoretinopathy (PVR), an inflammatory and fibrotic blinding disease, is still a therapeutic challenge. Retinal pigment epithelial (RPE) cells dislodged in the vitreous play a central role in the PVR pathogenesis. To identify potential novel contributors to the pathogenesis of PVR, we investigated a profile of vitreous-induced changes in human RPE cells by RNA sequencing. The results showed that CD180 capable of regulating the interleukin (IL)-2 pathway was down-regulated at least five times and that IL13RA2 (IL 13 receptor subunit α2) was up-regulated more than three times in the vitreous-treated RPE cells. Importantly, our subsequent Quantitative PCR and western blot analyses verified these changes in CD180 and IL13RA2 revealed by the RNA sequencing. The discovery of CD180 and IL13RA2 involved in vitreous-stimulated changes in human RPE cells will improve our understanding of the molecular mechanisms by which PVR develops and provide potential targets for PVR therapeutics.